Prevalence and outcome of anaemia among pregnant women attending tertiary care hospital in Visakhapatnam - Paladugu, Radha Kumari; Pentakota, Srinivas Jagath; N., Sushma (International Journal Of Community Medicine And Public Health, 2017)
Background: Anaemia in pregnancy is now considered as a major public health problem, caused by iron deficiency. WHO has estimated that prevalence of anaemia in developed and developing countries in pregnant women is 14% in developed countries and 51 percent in developing countries and 65-75% in India. Various programmes regarding anaemia prophylaxis and maternal health have been implemented but still the prevalence of anaemia related complications among pregnant women continues to be high. Hence the present study was conducted to study the prevalence and pregnancy outcome as a result of anaemia in a tertiary care center in Visakhapatnam. Methods: A cross sectional descriptive study was carried out from June 2016 to August 2016 in the Department of Obstetrics and Gynecology among postnatal women in King George hospital, Visakhapatnam. A semi-structured questionnaire was prepared and information regarding age, socioeconomic status, parity, gestational age interval between pregnancies and outcome and complication of pregnancy were collected. Results: Mean age of study population is 22.4 years. Out of 100 women involved in the study 65 are from urban areas 29 from rural areas and 6 from tribal areas. Majority of the study population 66% were having HB% between 8-11% i.e. mild anaemia. When Outcome of pregnancy was seen in relation to anaemia majority of the women had live births (90%) followed by 7% IUDs and 2% still births. Conclusions: Majority of the women are in the age group of 20-24 years. Socioeconomic status is directly related to anaemic status of the women. Majority of the women had complication of puerperal sepsis.